Design, Implementation and Evaluation of Student-centric learning in Physiology - Shivayogappa. S. Teli; M. Senthilvelou; K. Soundariya; Deepika Velusami; Senthamil selvi. K; Mangani Mangalavalli. S (Tabriz University of Medical Sciences, 2021)
Background: The quality of teaching and learning in health education determines the competency of doctors produced and ultimately the patient care. Realizing the necessity of active learning at the undergraduate level, curricular reforms are crucial to ensure that students play an active role in their learning process and absorb the prerequisite qualities of a competent health professional. The current study aimed to implement and evaluate case-based learning in a physiology curriculum. Methods: The study included 150 first-year MBBS students using a mixed methods research design. A short lecture on anemia was followed by two sessions of case-based learning with a gap of one week. A structured questionnaire usinga 5-point Likert scale was used to collect students' perceptions. The internal consistency of the questionnaire had a Cronbach's alpha of 0.8. Faculty feedback was collected using a Focus Group Discussion. Results: Of 145 participants, 117 provided feedback. Students perceived that the case-based learning method promoted meaningful learning (83%); helped in the future application of knowledge (81%);helped to understand physiology concepts better (72%); improved studentteacher relationships (72%); was effective in understanding the anemia topic (71%); led to the development of problem-solving abilities (70%); encouraged teamwork (69%); motivated selfdirected learning (66%); and improved communication skills (65%). Faculty members suggested developing an assessment plan for future case-based learning sessions. Conclusion: According to student and faculty feedback, case-based learning is an effective, active teaching-learning tool that improves students' understanding of basic concepts, clinical knowledge, problem-solving abilities, teamwork, communication skills, student-teacher relationship, and self-directed learning.